Inverse eigenvalue problems for nonlocal Sturm-Liouville operators on a star graph - Nizhnik, L. P. (Methods of Functional Analysis and Topology, 2012)
We solve the inverse spectral problem for a class of Sturm–Liouville operators with singular nonlocal potentials and nonlocal boundary conditions on a star graph.